Extraction and determination of tussilagone from Farfarae Flos with online solid‐phase extraction–high‐performance liquid chromatography using a homemade monolithic cartridge doped with porous organic cage material. Issue 24 (1st November 2021) - Wang, Laisen; Liu, Miaomiao; Sun, Fanrong; Liu, Haiyan; Yan, Hongyuan; Bai, Ligai
Abstract: A solid‐phase extraction cartridge was fabricated using diallyl isophthalate as the monomer with the addition of porous organic cage material via in situ free‐radical polymerization in a stainless‐steel column. The resulting monolithic adsorbent exhibited a relatively uniform porous structure, a high specific surface area of 113.98 m 2 /g, and multiple functional chemical groups according to the characterization results. An online solid‐phase extraction–high‐performance liquid chromatography procedure was fabricated to extract and determine tussilagone from Farfarae Flos. The results show that the complex sample matrices can be removed in the solid‐phase extraction procedure. Simultaneously, tussilagone can remain, which can be subsequently switched to an octadecylsilane bonded analytical column. The methodological validation showed that the correlation coefficient was 0.9999 with a linear range of 0.6–200.0 µg/mL, the limit of detection was 0.2 µg/mL, the limit of quantification was 0.6 µg/mL, accuracy was 100.3–100.6%, and relative standard deviation of precision was ≤1.9%. The present monolithic cartridge exhibits good reusability of not more than 100 times. The real sample of Farfarae Flos was determined with a tussilagone content of 0.74 mg/g.